1978
DOI: 10.1177/000456327801500143
|View full text |Cite
|
Sign up to set email alerts
|

Excretory Patterns of Urinary Free 11-Hydroxycortico-Steroids and Total Oestrogens Throughout the Normal Menstrual Cycle

Abstract: SUMMARY The excretion of urinary free ll-hydroxycorticosteroids and total oestrogens was studied daily in morning urine specimens throughout the menstrual cycle of six normal women (age range 18-24 years). The follicular phase of the cycle was characterised by apparently random fluctuations in the excretion of urinary free corticosteroids. However, after the mid-cycle oestrogen peak there occurred a significant drop in corticosteroid excretion, which then rose to a peak eight to 10 days after ovulation and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…such as androgens and glucocorticoids (Vermeulen & Verdonck, 1976; M.S. Walker & McGilp, 1978). Yet, again, there is as much evidence against these hypotheses as there is for them (see Janowsky & Rausch, 1985;Rubinow& Roy-Byrne, 1984).…”
Section: Biological Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…such as androgens and glucocorticoids (Vermeulen & Verdonck, 1976; M.S. Walker & McGilp, 1978). Yet, again, there is as much evidence against these hypotheses as there is for them (see Janowsky & Rausch, 1985;Rubinow& Roy-Byrne, 1984).…”
Section: Biological Explanationsmentioning
confidence: 99%
“…Other researchers have suggested that depressive symptoms in the premenstrual, postpartum, and menopause phases may result from excess prolactin levels (see Rubinow & Roy-Byrne, 1984) or from fluctuations in the adrenocortical hormones, such as androgens and glucocorticoids (Vermeulen & Verdonck, 1976; M.S. Walker & McGilp, 1978).…”
Section: Explanations For the Sex Differences In Depressionmentioning
confidence: 99%
“…However, none of the women exhibited UFCjCr ratios above the normal range at any time throughout the menstrual cycle (Walker and McGilp, 1978). In cases of frank Cushing's syndrome, the UFCjCr ratio gives a clear distinction between the normal and pathological group, UFCjCr ratios of over ]00 p.mol/mol being diagnostic for Cushing's syndrome.…”
Section: Discussionmentioning
confidence: 90%
“…Against this possibility is the observation that these hormones do not change dramatically during the menstrual cycle. Nevertheless, since cortisol may increase and androgens may decrease somewhat premenstrually (Vermeulen & Verdonck, 1976;Walker & McGilp, 1978), it is at least possible that an adrenal steroid could trigger central events, leading to the onset of PMT.…”
mentioning
confidence: 99%